THE ESSENTIALISM OF ISLAMIC RELIGIOUS EDUCATION IN SHAPING THE CHARACTER OF PANCASILA STUDENTS - Ali, Fiki Amalia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze the effectiveness of essentialism approach in Islamic religious education towards character building of Pancasila students in Indonesian schools. Using qualitative methods, this study explores teachers' perceptions and practices in integrating Pancasila values in Islamic religious education materials. Data were collected through in-depth interviews, classroom observation, and analysis of educational documents in several high schools. The results showed that teachers effectively implemented the values of Pancasila through an essentialism approach, which not only increased students' understanding of religious values but also nationality. The research also identified challenges such as under-resources and the need for more in-depth teacher training. Based on these findings, the study recommends the development of more comprehensive educational resources and teacher training to optimize the application of Pancasila values in Islamic religious education. This research provides new insights into the application of character education in the context of Indonesian national education, emphasizing the importance of integrating Pancasila values in the religious education curriculum to shape the holistic character of students.